Avalia????o da atividade de metaloproteinases e serinoproteinases na saliva de pacientes com Doen??a Pulmonar Obstrutiva Cr??nica (DPOC) - Basso, Juliana Gerunda (2009)
The present study was conducted to evaluate the activity of enzymatic components of saliva and possible correlations with clinical parameters in patients with COPD. The sample consisted of 30 individuals, 20 individuals with COPD and 10 controls. The clinical parameters of each individual were obtained by spirometry and 6 minute walk distance. Enzyme activity (EA) in saliva samples from each individual was evaluated in vitro using fluorescent substrates and synthetic inhibitors of metalloproteinases (EDTA) and serine proteinases (PMSF). There was no significant difference between patients with COPD and healthy relationship with the AE or total inhibition of metalloproteinases and serine proteinases in saliva. Analysis of correlations between variables Person of the clinical evaluation of COPD and the AE tests showed that the FEV1 correlated negatively to total EA (p=0.03, r =-0.473) and inhibition of metalloproteinases (p=0.02, r =-0.498). There was no correlation between the parameters evaluated in the control group. These results open perspectives for studies of enzyme kinetics in saliva, using specific substrates for enzymes most representative during the progression of COPD.